Effect of Prenatal Alcohol Exposure on Bony Craniofacial Development: A Mouse MicroCT Study - Shen, Li (2013)
Craniofacial bone dysmorphology is an important but under-explored potential diagnostic feature of fetal alcohol spectrum disorders. This study used longitudinal MicroCT 3D imaging to examine the effect of prenatal alcohol exposure on craniofacial bone growth in a mouse model. C57BL/6J dams were divided into 3 groups: alcohol 4.2% v/v in PMI(®) liquid diet (ALC), 2 weeks prior to and during pregnancy from embryonic (E) days 7-E16; pair-fed controls (PF), isocalorically matched to the ALC group; chow controls (CHOW), given ad libitum chow and water. The MicroCT scans were performed on pups on postnatal days 7 (P7) and P21. The volumes of the neurocranium (volume encased by the frontal, parietal, and occipital bones) and the viscerocranium (volume encased by the mandible and nasal bone), along with total skull bone volume, head size, and head circumference were evaluated using general linear models and discriminant analyses. The pups in the alcohol-treated group, when compared to the chow-fed controls (ALC vs. CHOW) and the isocaloric-fed controls (ALC vs. PF), showed differences in head size and circumference at P7 and P21, the total skull volume and parietal bone volume at P7, and volume of all the tested bones except nasal at P21. There was a growth trend of ALC < CHOW and ALC < PF. While covarying for gender and head size or circumference, the treatment affected the total skull and mandible at P7 (ALC > CHOW), and the total skull, parietal bone, and occipital bone at P21 (ALC < CHOW, ALC < PF). While covarying for the P7 measures, the treatment affected only the 3 neurocranial bones at P21 (ALC < CHOW, ALC < PF). Discriminant analysis sensitively selected between ALC and CHOW (AUC = 0.967), between ALC and PF (AUC = 0.995), and between PF and CHOW (AUC = 0.805). These results supported our hypothesis that craniofacial bones might be a reliable and sensitive indicator for the diagnosis of prenatal alcohol exposure. Significantly, we found that the neurocranium (upper skull) was more sensitive to alcohol than the viscerocranium (face).